The Effects of Audit Firm Size, Audit Tenure, and Audit Rotation on Audit Quality - Kautsar Riza Salman; Bety Setyaningrum (Yayasan Ilomata, 2023)
This study examines the effect of audit firm size, audit period, and audit rotation on audit quality. The data come from annual reports of infrastructure, utilities and transportation companies listed on the Indonesia Stock Exchange (IDX) from 2016 to 2020. The sampling method used is purposive sampling. A sample of 267 companies was obtained based on the purposive sampling method. The analysis technique used is logistic regression analysis with SPSS software. This study's results confirm agency theory's role in explaining the relationship between parties with different interests. The research findings reveal that the role of audit professional services performed by audit firms can minimize agency problems that arise. Empirically, study findings show that the size of an audit firm and its audit period positively affect audit quality. Conversely, audit rotation does not affect audit quality. The study results provide a practical contribution so that non-big-4 audit firms can improve audit quality as big-4. Audit firms should also pay attention to sufficient audit tenure, short enough or too long, to produce good audit quality.